Market Size and Supply Disruptions : Sharing the Pain of a Potential Russian Gas Shut-off to the European Union - Albrizio, Silvia (IMF Working Papers; Working Paper, 2022)
We assess the supply-side effects on European Union (EU) economic activity if Russian gas imports were to suddenly cease. Unlike other studies, we account for the global scope of the liquefied natural gas (LNG) market. In the absence of frictions, an open-economy, multi-sector general equilibrium model suggests that the adverse economic impact on the EU shrinks five-fold if integration with the global LNG market is considered. While greater integration provides a buffer for the EU through trade, the flip side is that other LNG importers (such as Japan, South Korea, and Pakistan) see adverse effects from higher prices.